Evaluation of applying chest pain guidelines in coronary care patients on their health outcome - Shahin, Eman; Hasan, Mona (International Journal of Advanced Nursing Studies, 2017)
Background: the National Heart, Lung, and blood Institute estimate that each year approximately 785,000 Americans will have a new coronary attack and approximately 470,000 will have a recurrent attack. Chest pain is one of the most common symptomsÂ Â of coronary artery disease or acute coronary syndrome. Objectives: this study aims to compare between routine nursing care of chest pain and chest pain guidelines in patients with acute coronary syndrome and assess health outcome after application of chest pain guidelines in acute coronary syndrome patients. Method: Quasi experimental research design was used in the current study. The study was conducted at the coronary care unit of Suez canal University Hospital. Sample; consecutive of 70 patients was included in the study. Â Four tools were used for study data collection that named the chest pain guidelines evidence based nursing care in patients with angina pectoris, visual analog scale to assess chest pain, dyspnea scale to assess breathing pattern and fourth one was lab investigation to assess patient health prognosis. Results: The study results revealed an improvement of patientsâ€™ health outcome represented in a significant reduction in complain of chest pain, blood pressure and insufficient sleeping with P-value of 0.000 after applying guidelines of care regarding chest pain. Additionally, the respiratory pattern and respiratory rate improved significantly with P-value of 0.000. Moreover, lab investigation showed significantly decrease in LHD level with P-value of 0.000. Conclusion: The current study concluded that application of chest pain guidelines intervention could be improved patients health outcomes.Â Â Â Â Â